2000
DOI: 10.4088/pcc.v02n0201
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Spectrum Disorders in the Primary Care Setting

Abstract: Dissociative disorders have a lifetime prevalence of about 10%. Dissociative symptoms may occur in acute stress disorder, posttraumatic stress disorder, somatization disorder, substance abuse, trance and possession trance, Ganser's syndrome, and dissociative identity disorder, as well as in mood disorders, psychoses, and personality disorders. Dissociative symptoms and disorders are observed frequently among patients attending our rural South Carolina community mental health center. Given the prevalence of men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Most of such cases are probably ignored as subthreshold in the catastrophic situations in the aftermath. Physicians and other professionals who take care of victims of disaster should be aware of such dissociative spectrum disorders [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of such cases are probably ignored as subthreshold in the catastrophic situations in the aftermath. Physicians and other professionals who take care of victims of disaster should be aware of such dissociative spectrum disorders [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such spirits include the "chen" in Uganda in the last example or those responsible for the "nightmare death" described in Hmong survivors of the Vietnam war (103,104). Rituals to appease the ghost and resolve the internal conflict and feeling of unfulfilled obligation are consequently common and would be added to or replace treatment (105,106) but might be interrupted in war or displacement. Culture specific explanatory models for symptoms or illness must also be considered (111), as symptoms for example of PTSD might be attributed not to torture, but to other including metaphysical problems like witches or spirits (112).…”
Section: Understanding the Cultural Background In The Assessment Of Vmentioning
confidence: 99%
“…Dissociative symptoms have been described in situations of acute stress, post‐traumatic stress disorder, somatization disorder, substance abuse, trance, Ganser syndrome, psychoses and personality disorders . Dissociative symptoms may be negative, positive, psychoform, or somatoform, or may be associated with alteration of consciousness .…”
Section: Reportmentioning
confidence: 99%
“…A dissociative state indicates that the person is detached from reality, and the condition is on a spectrum, ranging from a defence mechanism to altered states of consciousness. Dissociative symptoms may surface during periods of acute interpersonal or situational difficulties . It is suggested that traumatic experiences cause dissociative symptoms as an adaptive response, and scores on the Dissociative Experiences Scale are closely correlated with childhood trauma…”
Section: Reportmentioning
confidence: 99%